Gasless vNOTES vs. traditional vNOTES for benign gynecological disease: a randomized controlled clinical trial - Yanjun Wang; Kai Liu; Zhaolin Gong; Qinghua Huang; Qianqian Zhang; Dan Feng; Jiaojiao Chen; Ang Mao; Xia Yu; Lin Zhang; Yu Cui; Li He; et al. (BMC Anesthesiology)
Abstract Background Gasless transvaginal natural orifice transluminal endoscopic surgery (G-vNOTES) can avoid complications related to pneumoperitoneum, but there is limited research on G-vNOTES. Here, we aimed to compare the hemodynamic profiles and outcomes of G-vNOTES with traditional vNOTES (T-vNOTES) in the treatment of patients with benign gynecologic disease. Methods A total of 120 patients with benign gynecologic disease were randomly assigned to G-vNOTES (n = 60) or traditional vNOTES (n = 60). The primary outcome was vital sign at different time points. Secondary outcomes included conversion rate, surgical time, anesthesia time, the usage of anesthetics, estimated intraoperative blood loss, visual analogue scale (VAS) score for abdominal and shoulder pain and postoperative nausea and vomiting (PONV) at 2 and 24 h, intraoperative and postoperative complications, time to first anal exhaust, eating, and getting out of bed after surgery, and length of postoperative hospital stay. Multi-level model analysis was used for intraoperative hemodynamic indicators. Results There was no significant difference between the two groups at the baseline level. The results of the multilevel model indicate that there is no difference in intraoperative hemodynamic performance between the G-vNOTE group and the T-vNOTES group. The conversion rate in the G-vNOTES group was higher than that in the T-vNOTES group (16.95% vs. 5.26%, p = 0.046). No significant differences were observed in other areas. Conclusions This study did not find advantages of gasless vNOTES in intraoperative hemodynamic fluctuations. The surgical conversion rate of the G-vNOTES group is higher than that of the T-vNOTES group, which may be related to poor surgical field exposure in the G-vNOTES group, making it more suitable for experienced and confident surgeons.